An aerobic heterotrophic bacterial count of hatchery reared eggs, larvae and postlarvae of prawn, Penaeus monodon and their rearing waters. - Gamosa, Lobella Diamante (1995.)
This study focused on the relationship of the aerobic heterotrophic count and hatching rate of eggs and survival rates of larvae and postlarvae of prawn, Penaeus monodon. There was a gradual increase in the aerobic heterotrophic bacterial count (1.0x10 raised to the 1st power to 3.0x10 raised to the 3rd power cfu/ind) from eggs to postlarvae of prawn samples. The count increased from eggs to protozoa ( 1.0x10 raised to the 1st power to 4.4x10{FD} cfu/ind), but decreased in mysis stage (1.7x10{FD} cfu/ind) and again increased in the postlarval stage (3x10 raised to the 3rd power cfu/ind). The aerobic hetetrophic bacterial load in the rearing water ranged from 1.5x10{FD} to 1.2x10 raised to the 3rd power cfu/ml. In the water reservoir, the bacterial load ranged from 1.0x10 raised to the first power to 1.0x10 raised to the 3rd power cfu/ml and in the raw seawater, from 1.1x10{FD} to 5.1x10{FD} cfu/ml. There was a strong correlatioon between the aerobic heterotrophic bacterial count and hatching rate of eggs and survival rates of larvae and postlarvaeof P. monodon (r{FD} =0.84; alpha = 0.05). Significantly, the increase in the bacterial load has lowered the survival of the larvae and postlarvae of prawn. An increase in the bacterial population of P. monodon and its sorrounding environment could affect adversely its survival. The increase in the bacterial load is a good indicator of infection and stress and corrective measures should be adopted immediately to counteract the infection and stress.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Prawn; Penaeus monodon